Left ventricular remodelling pattern and prognostic relevance in patients with STEMI treated with primary percutaneous coronary intervention. (25th November 2020) - Chimed, S; Van Der Bijl, P; Lustosa, R; Montero, J.M; Marsan, N.A; Delgado, V; Bax, J.J
Abstract: Background: Left ventricular (LV) remodelling after ST-segment elevation myocardial infarction (STEMI) is a complex pathological process which has been associated with long-term cardiovascular adverse events. The current definition of LV remodelling is usually based on the change in LV end-diastolic volume (LVEDV). An increase in LVEDV, however, may also be considered an adaptive response to maintain effective LV ejection fraction (LVEF) in LV remodelling. Purpose: To reclassify post-infarct LV remodelling according to the change in LVEDV and LVEF from baseline and to determine the prognostic relevance of integrated LV remodelling and systolic function groups. Methods: A total of 1859 patients with STEMI who received primary percutaneous coronary intervention (PCI) and guideline-directed medical treatment, were retrospectively evaluated. Four LV remodelling subgroups were identified, based on the change in LVEDV and LVEF from baseline to 6 months post-infarct. ≥20% increase in LVEDV, compared to baseline, was defined as LV dilatation, while any increase or decrease in LVEF compared to baseline was used to categorise remodelling further according to systolic function. Study endpoints were all-cause mortality and the composite of all-cause mortality and heart failure (HF) hospitalisation. Results: The mean age of the study population was 60±11 years and the majority were men (76.4%). 402 patients showed LVEDV≥20% and LVEF increase (Group 1), 952 patients LVEDV≤20% and LVEF increase (Group 2), 325 patients LVEDV≤20% and LVEF decrease (Group 3) and 180 patients LVEDV≥20% and LVEF decrease (Group 4). During a median follow-up of 89 (IQR 64; 113) months, all-cause mortality occurred in 256 patients (13.8%), HF hospitalisation in 40 patients (2.2%) and the composite endpoint in 279 patients (15.0%). All-cause mortality was significantly higher in Group 4 (21.7%, chi-square p=0.002) compared to other groups (15.4% in Group, 12.9% in Group 2 and 9.8% in Group 3). The composite endpoint was also significantly more frequent in Group 4 (25.6%, chi-square p<0.001) compared with the other groups (16.2% in Group 1, 13.8% in Group 2 and 11.4% in Group 3). Mean survival time (Figure 1A) and event-free survival time for the composite endpoint (Figure 1B) were significantly lower in Group 4 (122 months 95% CI 115–128, p=0.004 and 117 months 95% CI 110–124, p<0.001, respectively) compared to other groups. Conclusion: Patients with LVEDV≥20% and a LVEF decrease at 6 months after STEMI experienced all-cause mortality and the composite endpoint of all-cause mortality and HF hospitalisation more frequently compared to other LV remodelling groups. Patients with an increase in LVEDV and a decrease in LVEF 6 months after STEMI, may benefit from careful surveillance and preventative strategies. Funding Acknowledgement: Type of funding source: None